Wolf Tracks : Popular Art and Re-Africanization in Twentieth-Century Panama - Szok, Peter A., 1968- (Book collections on Project MUSE., 2012)
Popular art is a masculine and working-class genre, associated with Panama's black population. Its practitioners are self-taught, commercial painters, whose high-toned designs, vibrant portraits, and landscapes appear in cantinas, barbershops, and restaurants. The red devil buses are popular art's most visible manifestation. The old school buses are imported from the United States and provide public transportation in Colón and Panama City. Their owners hire the artists to attract customers with eye-catching depictions of singers and actors, brassy phrases, and vivid representations of both loc.